A male patient with amyand hernia: A case report and literature review (Indian Journal of Case Reports, 2024)
An Amyand hernia is a protrusion of an organ or its fascia through the wall of the abdominal cavity which contains the appendix, which has an incidence rate of 0.5–1% of the many hernia cases. This review reports the case findings of a 63-year-old male patient with an inguinal hernia containing the appendix (Amyand hernia). The patient came with complaints of abdominal pain and a lump in his testicles, with a history of frequent lumps coming and going. Physical examination from the right inguinal to the scrotal sac found a lump the size of three adult fists with the same skin color as the surroundings. The patient was diagnosed with a giant right scrotal hernia and underwent herniorrhaphy surgery and mesh placement. During the operation, the appendix and mesoappendix were visible upon opening the hernia sac, so it was decided to perform an appendectomy, return the contents of the hernia sac into the abdominal cavity, and do a mesh installation. Amyand hernia itself presents a diagnostic challenge because of its low incidence, vague clinical signs and symptoms, and lack of clear radiological diagnostic features. In addition, there are still no clear guidelines for its management.